2017
DOI: 10.1155/2017/8392035
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity Study of Cyclopentapeptide Analogues of Marine Natural Product Galaxamide towards Human Breast Cancer Cells

Abstract: Herein, we report the cytotoxicity of cyclopentapeptide analogues of marine natural product galaxamide towards breast carcinoma cells and the underlying mechanisms. We examined the effect of the novel galaxamide analogues on cancer cell proliferation by MTT assay and also further examined the most active compound for morphological changes using Hoechst33342 staining technique, induction of apoptosis, cell cycle phases, mitochondrial membrane potential (MMP), and reactive oxygen species (ROS) generation using f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…and Phakellia costata [ 27 ]. Cyclic peptides obtained from algae are galaxamide compounds isolated from the marine algae Galaxaura filamentosa [ 28 ]. In addition to these naturally derived cyclic peptides, many more have been chemically synthesized: one example is bacillistatin [ 29 ].…”
Section: Structure and Source Of Cyclic Peptidementioning
confidence: 99%
“…and Phakellia costata [ 27 ]. Cyclic peptides obtained from algae are galaxamide compounds isolated from the marine algae Galaxaura filamentosa [ 28 ]. In addition to these naturally derived cyclic peptides, many more have been chemically synthesized: one example is bacillistatin [ 29 ].…”
Section: Structure and Source Of Cyclic Peptidementioning
confidence: 99%
“…Galaxamide ( 72) was a representative algae-derived cyclic pentapeptide discovered in marine algae Galaxaura filamentosa, which showed moderate inhibitory activities against Galaxamide ( 72) was a representative algae-derived cyclic pentapeptide discovered in marine algae Galaxaura filamentosa, which showed moderate inhibitory activities against GRC-1 (human renal cell carcinoma, IC 50 = 7.18 µM) and HepG2 (IC 50 = 7.81 µM) cell lines [119]. In the study of Lunagariya et al [120], they investigated the mechanism of action of galaxamide on MCF7 cells in detail. Their results demonstrated that galaxamide induced apoptosis via the oxidative stress-mediated signaling pathway, by which the mitochondrial membrane potential was disrupted in response to the overwhelmed production of reactive oxygen species (ROS).…”
Section: Anticancer Cyclopeptides Derived From Marine Algaementioning
confidence: 99%
“…The deprotected hydrochloride salt of compound 5 was accomplished by dissolved it (5) in DCM followed by acidification with cold HCl and then stirring for 3-4 hours at room temperature. The diverse targeted motif, i.e., Tripeptide (7), was formed by coupling KSM-2 and6 (HCl salt) in the presence of EDC-HCl and DMAP at RT.…”
Section: Chemistrymentioning
confidence: 99%
“…Despite the intensive investigation of breast cancer cell lines, the cellular and molecular mechanisms between the MCF-7 cell line and the drug polyoxometalate (POM) are still limited [6]. Anticancer peptides (ACPs) have been proved to be effective small molecules (nearly 50 amino acids) that can act specifically against cancerous cells by either a membranolytic mechanism or disruption of mitochondria [7].…”
Section: Introductionmentioning
confidence: 99%